A Day in the Life of Clandestine Women War Workers at Casa Loma: Using Feminist Fiction-based Research to Pedagogically Peel Back Layers of Invisibility - Kitchin, Adrienne; Taber, Nancy (The Canadian Journal for the Study of Adult Education / La revue canadienne pour l’étude de l’éducation des adultes)

(untitled) (Canadian Association for the Study of Adult Education / L’Association canadienne pour l’étude de l’éducation des adultes, 2025)
In this article, we discuss the learning processes of our historical feminist fiction-based research which makes visible the often forgotten and essentialized stories of Toronto-based women World War II workers. We describe this gendered war work through the lenses of intersectional feminism and feminist antimilitarism. We detail the power of fiction-based research as feminist methodology and pedagogy, situating it within the sphere of feminist adult education scholarship. We explain our fiction-based research study which resulted in thematic vignettes from a day-in-the-life short story about women war workers involved in a clandestine project at Casa Loma. We conclude with implications of fiction-based research for feminist adult education.